Analisis Kinerja Fisik Bendung Irigasi Menggunkan Metode Analytic Hirarchy Process - Vionadwiuchtia Idrat; Darwizal Daoed; Nurhamidah Nurhamidah (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2021)
Dams aim to raise water from the average water level to the higher water level to be into rice fields located far from the river. Dams like this are called irrigation dams. An Irrigation dam with a small service scale of 3000 ha is a dam with a medium service level, and the function is the same as a large dam, but the physical and facilities are simpler. Moreover, the number of dams and remote locations makes it difficult to monitor, and it is necessary to make a priority scale for repairs. It can be made more accessible by prioritizing the restoration of each dam and ranking. Based on the above, research was conducted using the Analytical Hierarchy Process (AHP) on the components and sub-components of the dam. This study analyzes several dams in West Sumatra, namely Gunung Nago Dam in Kuranji District, Padang City, Banda Gadang Dam in Gunung Talang District, Solok Regency, Paneh Gadang Dam in Gunung Talang District, Solok Regency. Data collection techniques are carried out by direct observation to the field and questionnaires to resource persons who are water experts. The survey results and analysis showed a dam performance index from 1,2% to 2,7% with a low to moderate dam category and a level of vulnerability to dams from vulnerable - to moderately vulnerable. This result is an indication that higher performance values should be on priority for improvement. This method can be developed and used by policymakers to pay attention to dam performance.